The Most Hated Man in Kentucky : The Lost Cause and the Legacy of Union General Stephen Burbridge - Asher, Brad, 1963- (Book collections on Project MUSE., 2021)
"For the last third of the nineteenth century, Union General Stephen Gano Burbridge enjoyed the unenviable distinction of being the most hated man in Kentucky. From mid-1864, just months into his reign as the military commander of the state, until his death in December 1894, the mere mention of his name triggered a firestorm of curses from editorialists and politicians. By the end of Burbridge's tenure, Governor Thomas E. Bramlette concluded that he was an 'imbecile commander' whose actions represented nothing but the 'blundering of a weak intellect and an overwhelming vanity.' In this revealing biography, Brad Asher explores how Burbridge earned his infamous reputation and adds an important new layer to the ongoing reexamination of Kentucky during and after the Civil War. He explains that Burbridge's use of measures, including retaliatory executions, to quell guerrillas and Confederate partisans fell within the range of tactics used by Union commanders faced with irregular fighters in other areas and within the bounds of the laws of war as articulated by the Union high command. Burbridge jailed, banished, and harassed those who expressed anti-Lincoln, anti-war, or pro-Confederate political sympathies. Most importantly, however, he oversaw and sped along the destruction of slavery by administering the recruitment and enlistment of enslaved people as soldiers. This reassessment illuminates how Burbridge--as a Kentuckian and the local architect of the destruction of slavery--became the scapegoat for white Kentuckians, including many in the Unionist political elite, who were unshakably opposed to emancipation. Beyond successfully recalibrating history's understanding of Burbridge, Asher's biography adds administrative and military context to the state's reaction to emancipation and sheds new light on its postwar pro-Confederacy shift"--